Families, Drugs and Crime - Clutterbuck, Richard. author. aut Link
XVI, 224 p.
Keywords: Every mother and father is concerned about how to help her or his children to resist the temptations and pressures at school and amongst neighbourhood kids to get involved with petty crime or drugs. This book is about what parents should do from babyhood to teenage to cope with these hazards.